A configuração de forças na constituição histórica do trabalho como estratégia de cuidado em saúde mental: problematizações foucaultianas - Santiago, Eneida Silveira; Yasuí, Silvio [UNESP] (My University, 2013)
Investigated in this paper, as contributions to Foucault's genealogy of knowledge, the historical constitution of the joint activities between Work and Care in Mental Health (called Therapeutic Workshops, among other names) in their different purposes and dimensions that contributed to the production care of patients with psychological distress at different times. History is here understood as a multiplicity (and nonlinearity) of time series and various blending and shuffleforming speeches as truths. In conjunction we have discussed, we conclude that the work as a therapeutic modality in nursing homes, there emerged in the world of psychiatry, but of capitalism. Associated with measures of occupation "empty minds" of misfits, later earned the position of an instrument of discipline and social regulation. With the Psychiatric Reform, activities Work in Mental Health have been re-invented as spaces enablers of access to citizenship and contractuality social network users.

Investigamos neste texto, a partir das contribuições foucaultianas para a genealogia do saber, a constituição histórica da articulação entre atividades de Trabalho e Atenção em Saúde Mental (chamadas de Oficinas Terapêuticas, entre outros nomes) em seus diversos propósitos e dimensões que contribuíram para a produção do cuidado do portador de sofrimento psíquico em diferentes momentos. A História é aqui compreendida como uma multiplicidade (e não linearidade) de tempos e séries diversas que misturam-se e embaralham-se formando discursos proferidos como verdades. Na articulação que aqui discutimos, concluímos que o Trabalho como modalidade terapêutica nas instituições asilares, não surgiu no universo da psiquiatria, mas do capitalismo. Associado às medidas de ocupação de “mentes vazias” dos desajustados, mais tarde ganhou a posição de instrumento de disciplina e normatização social. Com a Reforma Psiquiátrica, as atividades de Trabalho na Saúde Mental foram re-inventadas como espaços possibilitadores de acesso à cidadania e contratualidade social dos usuários da rede.
Configuration of forces in the constitution of historical work as a strategy in mental health care: argumentation by foucault
Keywords: Mental health; Public Health; Genealogy; Labor relations; Subjectivity; Intersectoriality; Saúde mental; Saúde coletiva; Genealogia; Relações de trabalho; Subjetividade; Intersetorialidade